1997
DOI: 10.1016/s0896-6273(00)80937-x
|View full text |Cite
|
Sign up to set email alerts
|

Response Diversity and the Timing of Progenitor Cell Maturation Are Regulated by Developmental Changes in EGFR Expression in the Cortex

Abstract: Early cortical progenitor cells of the ventricular zone (VZ) differ from later progenitor cells of the subventricular zone (SVZ) in cell-type generation and their level of epidermal growth factor receptors (EGFRs). To determine whether differences in their behavior are causally related to EGFR number/density, we introduced extra EGFRs into VZ cells with a retrovirus in vivo and in vitro. This results in premature expression of traits characteristic of late SVZ progenitor cells, including migration patterns, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
250
0
7

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(291 citation statements)
references
References 83 publications
34
250
0
7
Order By: Relevance
“…The distinct actions exerted by TGFa on cortical neural progenitors, mitogenic or promoting an astrocytic fate according to the developmental stage, depend on the low or high expression levels of its receptor, respectively. During the late stage of embryonic development, when gliogenesis takes over neurogenesis, it favours the preferential differentiation of neural progenitors into astrocytes over neurons, an effect mediated by enhanced expression of erbB1, and segregation of the receptors into the daughter cell that will ultimately acquire an astrocyte phenotype (Lillien, 1995;Burrows et al, 1997;Sun et al, 2005). Interestingly, we observed that conversion of mature astrocytes into progenitor-like cells correlated with the downregulation of the wholecell erbB1 content, suggesting that modulation of the receptor levels might be part of the mechanisms by which TGFa alters the astrocyte phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinct actions exerted by TGFa on cortical neural progenitors, mitogenic or promoting an astrocytic fate according to the developmental stage, depend on the low or high expression levels of its receptor, respectively. During the late stage of embryonic development, when gliogenesis takes over neurogenesis, it favours the preferential differentiation of neural progenitors into astrocytes over neurons, an effect mediated by enhanced expression of erbB1, and segregation of the receptors into the daughter cell that will ultimately acquire an astrocyte phenotype (Lillien, 1995;Burrows et al, 1997;Sun et al, 2005). Interestingly, we observed that conversion of mature astrocytes into progenitor-like cells correlated with the downregulation of the wholecell erbB1 content, suggesting that modulation of the receptor levels might be part of the mechanisms by which TGFa alters the astrocyte phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…TGFa acts as a mitogenic or differentiating factor at different steps of the pathway leading from a neural stem cell to a mature astrocyte according to the low or high levels of erbB1 expressed by the cell (Lillien, 1995;Burrows et al, 1997;Sun et al, 2005). Any analysis of TGFa effects thus requires a careful characterization of the cell population studied.…”
Section: Introductionmentioning
confidence: 99%
“…30 In the developing forebrain, there is evidence that EGFR immunostaining is greatest in the SVZ 31,32 and that the generation of EGF-responsive stem cells between E13.5 and E15.5 in the mouse striatal granular zone, coincides with the formation of the SVZ, 33 highlighting the influence that EGF has on this proliferative niche.…”
Section: Dopamine Stimulates Svz Proliferation Via Egfmentioning
confidence: 99%
“…In vitro, single neural stem cells proliferate to form clonally derived floating sphere colonies (neurospheres), which contain cells that, upon dissociation into single cells, give rise to new sphere colonies (self-renewal) and cells that can differentiate into neurons or glia (multipotentiality). Fibroblast growth factor-2 (FGF2)-responsive neural stem cells first appear in vivo at embryonic day (E) 8.5 and a separate and additive population of epidermal growth factor (EGF)-responsive neural stem cells arises from the earlier born FGF2-responsive stem cells by asymmetric division between E11 and E13 (Burrows et al 1997;Mayer-Proschel et al 1997;Tropepe et al 1999). Both FGF2-responsive and EGF-responsive neural stem cells expand their populations and extend their cell cycle times during later embryogenesis (Martens et al 2000).…”
mentioning
confidence: 99%